Geocomputation techniques for spatial analysis: are they relevant to health data? - Gilberto Câmara; Antônio Miguel Vieira Monteiro (Cadernos de Saúde Pública)
Geocomputation is an emerging field of research that advocates the use of computationally intensive techniques such as neural networks, heuristic search, and cellular automata for spatial data analysis. Since increasing amounts of health-related data are collected within a geographical frame of reference, geocomputational methods show increasing potential for health data analysis. This paper presents a brief survey of the geocomputational field, including some typical applications and references for further reading.